Urban Bird Ecology and Conservation - Warren, Paige S. (Paige Shannon); Lepczyk, Christopher A. (Christopher Andrew), 1970- (Book collections on Project MUSE., 2012)
Now that more than half of the world's population lives in cities, the study of birds in urban ecosystems has emerged at the forefront of ornithological research. An international team of leading researchers in urban bird ecology and conservation from across Europe and North America presents the state of this diverse field, addressing classic questions while proposing new directions for further study. Areas of particular focus include the processes underlying patterns of species shifts along urban-rural gradients, the demography of urban birds and the role of citizen science, and human-avian i.